Integrating Islamic Values into English Curriculum Development: A Descriptive Qualitative Literature Review in State Islamic Higher Education - Chamisah (Barkah Publishing, 2025)
This systematic literature review explores the integration of Islamic values into English Language Teaching (ELT) at Islamic Higher Education Institutions (SIHE) in Indonesia. The study synthesizes findings from various academic sources to understand how Islamic principles such as trustworthiness, compassion, justice, and the oneness of God—are embedded into ELT curricula. Results indicate that while some SIHE have successfully implemented value-based language instruction through culturally relevant materials, classroom strategies, and teacher efforts, the overall integration remains inconsistent due to challenges such as limited teacher training, lack of instructional resources, and inadequate policy frameworks. The review concludes that a structured, collaborative approach is required to strengthen the integration process and recommends further empirical research to develop effective pedagogical models.